LRP1B mutations are associated with favorable outcomes to immune checkpoint inhibitors across multiple cancer types. Issue 3 (2nd March 2021) - Brown, Landon C; Tucker, Matthew D; Sedhom, Ramy; Schwartz, Eric B; Zhu, Jason; Kao, Chester; Labriola, Matthew K; Gupta, Rajan T; Marin, Daniele; Wu, Yuan; Gupta, Santosh; Zhang, Tian; et al.
Abstract : Background: Low-density lipoprotein receptor-related protein 1b (encoded by LRP1B ) is a putative tumor suppressor, and preliminary evidence suggests LRP1B- mutated cancers may have improved outcomes with immune checkpoint inhibitors (ICI). Methods: We conducted a multicenter, retrospective pan-cancer analysis of patients with LRP1B alterations treated with ICI at Duke University, Johns Hopkins University (JHU) and University of Michigan (UM). The primary objective was to assess the association between overall response rate (ORR) to ICI and pathogenic or likely pathogenic (P/LP) LRP1B alterations compared with LRP1B variants of unknown significance (VUS). Secondary outcomes were the associations with progression-free survival (PFS) and overall survival (OS) by LRP1B status. Results: We identified 101 patients (44 Duke, 35 JHU, 22 UM) with LRP1B alterations who were treated with ICI. The most common tumor types by alteration (P/LP vs VUS%) were lung (36% vs 49%), prostate (9% vs 7%), sarcoma (5% vs 7%), melanoma (9% vs 0%) and breast cancer (3% vs 7%). The ORR for patients with LRP1B P/LP versus VUS alterations was 54% and 13%, respectively (OR 7.5, 95% CI 2.9 to 22.3, p=0.0009). P/LP LRP1B alterations were associated with longer PFS (HR 0.42, 95% CI 0.26 to 0.68, p=0.0003) and OS (HR 0.62, 95% CI 0.39 to 1.01, p=0.053). These results remained consistent when excluding patients harboring microsatellite instability (MSI) and controlling for tumor mutational burden (TMB). Conclusions: This multicenter study shows significantly better outcomes with ICI therapy in patients harboring P/LP versus VUS LRP1B alterations, independently of TMB/MSI status. Further mechanistic and prospective validation studies are warranted.